ANALISIS PERUBAHAN POLA GENETIK EMPAT GENERASI MANGGIS (Garcinia mangostana L.) BERDASARKAN MARKA ISSR [Analysis of Genetic Pattern Changes among Four Generations of Mangosteen (Garcinia mangostana L.) Based on ISSR Marker] - Noorrohmah, Siti; Sobir, Sobir; Efendi, D. (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Mangosteen reproduces trough apomixes mechanism, from which the seed develops without fertilization. Mangosteen is an obligate apomicts and it is believed that all of its progenies may have the same genotype as their mother plant. However it was found that genetic variations occured among mangosteen accessions. This research is aimed to study of genetic changing among generations mangosteen. The plant materials used were four generations (P1, P2, P3, and P4) of mangosteen taken from Wanayasa, Purwakarta.The samples were selected according to tree height and taken from each sector (north, east, south, and west). Genetic observations were conducted using Inter Simple Sequence Repeat (ISSR) technique. Ten primers were used to amplify the genomic DNA of mangosteen. It was found that the genetics pattern differed among tree of different age. More variation was observed on the older mangosteen tree.This information may be useful to determine the optimum age of mangosteen for becoming mother plant.